QUALITY OF SORGHUM (Sorghum bicolor)-CALOPO (Calopogonium mucunoides) SILAGE WITH ADDITIONAL OF ORGANIC LACTIC ACID - Nur Santy Asminaya (Jambura Journal of Animal Science, 2023)
Sorghum is a forage that has low protein content, whereas calopo is a protein source feed. If sorghum and calopo are fermented, it makes it difficult to lower the pH so that the nutrient content is easily damaged. The aim of this study was to evaluate the physical and chemical quality of fermented silage in combination between sorghum (Sorghum bicolor) and calopo (Calopogonium mucunoides) which were added with different levels of lactic acid. The ratio of the combination of sorghum and calopo as ingredients for silage is 40: 60%. Silage is made in 1 liter silo which is fermented for 21 days. This study used a completely randomized design (CRD) with 5 treatments (control and 4 levels of lactic acid addition, namely 1, 2, 3 and 4%) and 4 replications. Parameters observed included color, aroma, texture, pH, dry matter (BK), Fleigh value (NF), crude fiber (CF), and crude protein (CP). The results showed that the increase in the percentage of lactic acid use showed good physical quality (brown yellow color, citrus aroma and crumb texture) of silage. Chemically, the higher the level of addition of lactic acid to the sorghum-calopo silage, the BK content increased from 17.84% to 20.53%, decreased pH from 4.93 to 4.0 and increased NF from 43.33 to 86.0. The conclusion in this study was the use of lactic acid up to 4% in the silage of the combination of sorghum and calopo still showed good quality as indicated by NF 86 and pH 4.00